Conservation agriculture and nutrient management strategies for enhancing crop performance, productivity and nutrient uptake under rice-wheat cropping system - Ranjan, Shivani; Roy, Dhirendra Kumar; Pramanick, Biswajit; Singh, Santosh Kumar; Kavita; Jha, Prem Kumar (Plant Science Today, 2024)
Understanding the relationship between tillage and nutrient management strategies is crucial for maintaining the long-term sustainability of the rice-wheat cropping system (RWCS). Therefore, a field experiment was conducted from 2022 to 2024 at Dr. Rajendra Prasad Central Agricultural University in Pusa, Samastipur, Bihar to study the effect of nutrient management strategies under conservation agriculture (CA) for enhancing crop growth performance, protein content and productivity of RWCS. The experiment was conducted in a split-plot design replicated thrice with 3 different tillage and crop establishment methods [zero tillage direct seeded rice (ZTDSR)-zero tillage wheat (ZTW), puddled DSR (PDSR)-ZT with rice residue retention (ZT + RR) and puddled transplanted rice (PTR)-conventional tillage wheat (CTW)] in main plots and four nutrient management strategies [Farmer’s Fertilizer Practices (FFP), Nutrient Expert recommended dose of fertilizer (NE-RDF), RDF + spray of nanourea (NU) and Customized fertilizer (CF)] in sub plots. In both years, crop growth attributes at harvest in rice were found maximum under PDSR while in wheat it was under ZT + RR. In wheat, ZT + RR recorded maximum grain yield which was 13 % and 14.5 % higher than CTW in 2022-23 and 2023-24 respectively. A decline in rice grain yield of 8.3 % and 8.9 % was recorded under FFP over NE-RDF in 2022 and 2023 respectively. Hence, PDSR followed by ZT+RR coupled with NE-RDF can increase agronomic performance and productivity under RWCS.